Neonatal acute kidney injury in a tertiary care hospital in Kashmir, Jammu and Kashmir, India - Ashraf, Mohd; Bhat, Firdous Ahmed; Tak, Shafat Ahmed; Iqbal, Javaid; Kambay, Altaf Hussain; Riyaz, Anisa (Indian Journal of Child Health, 2019)
Background: Acute kidney injury (AKI) is a common entity in neonates admitted to the neonatal intensive care unit (NICU). Neonatal AKI is associated with increased morbidity and mortality and a greater risk of chronic kidney disease among the affected ones in future. Objectives: The objectives of this study were to study the incidence and outcome of neonatal AKI in our NICU. Materials and Methods: This single-center retrospective study included all infants who were admitted in a tertiary care hospital, J and K, from June 2013 to May 2014. Neonates, who had known congenital kidney diseases or if they did not survive beyond the first 48 h of life or had a hospital stay for <24 h, were excluded from the study. AKI was defined according to the kidney disease: Improving global outcomes criteria. Both AKI and non-AKI neonates were followed up until NICU discharge. Outcomes studied included mortality and length of NICU stay. Results: A total of 1439 neonates were studied among whom 72.89% (1049/1439) were normal weight, 11.46% (165/1439) were low birth weight, and 15.63% (225/1439) were very low birth weight. Of 1436 studied, 72% (1036) were term babies and 28% (403) were preterm babies. Perinatal asphyxia accounted for 43% (620/1439), seconded by neonatal sepsis 31.6% (455/1439) as a cause of NICU admission. Incidence of neonatal AKI in our study was 8.33% (120/1439). Mortality rate among the neonatal AKI patients was 34.1% (41/120). Conclusion: Our study shows an incidence of 8.3% among the NICU patients with a high mortality rate of 34.1%, implying a heightened awareness and very close monitoring of renal function during hospitalization and after discharge in such infants.